Evaluation of Vascular Activity in Otosclerosis by Laser‐Doppler Flowmetry: Comparison with CT Densitometry. (23rd August 2013) - Sone, Michihiko; Yoshida, Tadao; Suga, Kenji; Kato, Ken; Otake, Hironao; Teranishi, Masaaki; Nakashima, Tsutomu
Abstract : Objectives: Evaluate vascular activity in ears with otosclerosis by intraoperative measurement of blood flow using laser‐Doppler flowmetry, and compare the data with densitometry on computed tomography (CT). Methods: Thirty‐nine ears from patients who underwent surgery for otosclerosis were assessed in the present study. The subjects were divided into the fenestral (29 ears) and the retrofenestral (10 ears) groups by CT. Ratios of bone density in the area anterior to the oval window (AOW) or the promontory (PT) near the round window niche to that of the basis labyrinthine otic capsule were calculated on CT images. Measurements of blood flow were performed with a laser‐Doppler flowmeter at the two corresponding areas evaluated by CT. Results: In both groups, relatively young subjects with high blood flow values in the AOW or PT had rather low ratios of bone density in the corresponding areas. In contrast, old subjects with low ratios of bone density showed low blood flow values in the same areas. In the retrofenestral group, subjects with high blood flow values in the PT showed low blood flow values in the AOW, but their ratios of bone density were similarly low in both areas. Conclusions: Blood flow varied and did not correlate with CT densitometry. Measurement of blood flow by laser‐Doppler flowmetry could yield useful information to evaluate the progress of vascular activity.